Lightning safety psyche - Gomes, Chandima; Gomes, Ashen (IEEE, 2016)
How is lightning protection ranked in the field of safety science? What is the general perception of the public with regard to the risk of receiving a lightning strike to their building? How do business entities manipulate the psyche of the public in upsizing financial gains? What is the true risk of public adopting lightning protection techniques that have not been included in major international standards? Is the research presented so far in condemning the lightning protection systems rejected by the scientific community, well-conducted? Is tabooing of some lightning protection technologies a productive strategy in driving the public to adopt protection systems recommended by international (IEC) standards? This paper makes comprehensive attempts to answer these questions.